Evidence That Investors Trade on Private Event-Period Information around Earnings Announcements - Barron, Orie E.; Harris, David G.; Stanford, Mary (The Accounting Review, 2005)
Holthausen and Verrecchia's (1990) and Kim and Verrecchia's (1997) theoretical models predict that private information inferred at the time of an earnings announcement (private event-period information) is associated with greater trading volume. We provide empirical evidence consistent with these theories. Specifically, announcements that increase analysts' private information (as measured by Barron et al.'s [1998] empirical proxies) are associated with increased trading volume, consistent with some investors similarly acquiring private event-period information. In addition, announcements that decrease analysts' consensus are associated with more trading volume. Because consensus declines when private information increases, this finding provides reinforcing evidence that investors trade following earnings announcements because of private information that becomes useful only in conjunction with the information in the announcement and that this information is important enough to spur trading.